2020
DOI: 10.1016/j.jtauto.2019.100031
|View full text |Cite
|
Sign up to set email alerts
|

Periodic fever syndromes and the autoinflammatory diseases (AIDs)

Abstract: Innate immune system represents the ancestral defense against infectious agents preserved along the evolution and species; it is phylogenetically older than the adaptive immune system, which exists only in the vertebrates. Cells with phagocytic activity such as neutrophils, macrophages, and natural killer (NK) cells play a key role in innate immunity. In 1999 Kastner et al. first introduced the term “autoinflammation” describing two diseases characterized by recurrent episodes of systemic inflammation without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 227 publications
(291 reference statements)
0
13
0
4
Order By: Relevance
“…Recently, Carapito R. et al reported the case of two sisters with the same mutation (V377I/V377I) but showing different clinical manifestations: one sister was asymptomatic and the other was symptomatic due to the presence of a gain of function mutation of STAT1 gene (c.722G > A-p.Arg241Gln), influencing the phenotype [51]. This finding could provide therapeutic options through inhibition of the JAK/STAT pathway [52].…”
Section: Mevalonate Kinase Deficiency (Mkd)mentioning
confidence: 92%
“…Recently, Carapito R. et al reported the case of two sisters with the same mutation (V377I/V377I) but showing different clinical manifestations: one sister was asymptomatic and the other was symptomatic due to the presence of a gain of function mutation of STAT1 gene (c.722G > A-p.Arg241Gln), influencing the phenotype [51]. This finding could provide therapeutic options through inhibition of the JAK/STAT pathway [52].…”
Section: Mevalonate Kinase Deficiency (Mkd)mentioning
confidence: 92%
“…Over the last 2 decades due to an increasing awareness and availability of high throughput genetic sequencing techniques, there has been an exponential increase in discovery of genes responsible for SAID ( 2 , 12 , 13 ). Further, molecular insights of these disorders have provided the basis for new therapeutic interventions leading to improved outcomes and long-term survivals.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic autoinflammatory diseases (SAID) are complex inherited disorders caused by defects in several genes regulating innate immune signaling and are characterized by periodic or chronic multisystem sterile inflammation (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…3 Familial Mediterranean Fever (FMF) is the most common monogenic autoinflammatory disease, particularly in the Mediterranean. 4 FMF is characterized by recurrent systemic inflammatory attacks with fever and serositis. Periyodik Ateş, Aftöz Stomatit, Farenjit, Servikal Adenit Sendromu (PFAPA), which not known genetic defect still is another SAID wide range of worldwide.…”
Section: Introductionmentioning
confidence: 99%